Performance-based-maintenance: a comparative study between the Netherlands and Israel - Shohet, Igal M.; Straub, Ad (International Journal of Strategic Property Management, 2013)
Traditional maintenance contracts using the unit price system and prescriptive specifications are simple in their structure and implementation. Implementation of prescriptive-based specification reduces though the flexibility of the procurement and limits the possibilities of the contractor to improve the in-sight operation. Furthermore, the management of the contract faces difficulties such as poor performance of the buildings and ineffective contract management. Performance-Based-Maintenance (PBM) attains an alternative means for outsourcing of maintenance. The objective of the study was to comparatively assess the state-of-the-art of PBM between the Netherlands and Israel, with the focus on performance of public facilities and cost of the service. Pilot studies, carried out in the Netherlands and Israel, reveal that PBM attains high potential of cost-savings (20%) and improved performance. The paper concludes with provision of a future bidding system for PBM contracts. First Publish Online: 27 Jun 2013